Carboxymethyl cellulose synthesis from durian seed flour: The effect of sodium chloroacetate variation. Issue 1 (March 2021) - Ginting, MHS; Utama, A; Muhammad, H; Maulida,; Tambun, R
Abstract: Carboxymethyl Cellulose (CMC) is cellulose derivate that is soluble in water, CMC is synthesized by reacting cellulose with sodium hydroxide and chloroacetate acid or its salt. This study purpose is to see the effect of sodium chloroacetate salt in carboxymethylation reaction to the CMC degree of substitution. To test the quality of the CMC product, the analysis that is conducted in this study are: degree of substitution analysis as written in ASTM D 1439, FTIR, and SEM-EDX. The best result that is got from this study is producing the CMC with degree of substitutions of 0.42 with addition of 3 gr sodium chloroacetate salt.